Systematic investigation of ethanolic extract from Leea macrophylla: Implications in wound healing. (15th September 2016) - Joshi, Apurva; Joshi, Vinod K.; Pandey, Deepali; Hemalatha, S.
Abstract: Ethnopharmacological relevance: Leea macrophylla Roxb. ex Hornem. (Leeaceae) commonly known as Hastikarnapalasa is mainly distributed throughout the tropical parts of India. Traditionally, the plant is found to be effective against guinea worm, ringworm and is applied to sores and wounds. Aim of the study: The present study aims to validate traditional wound healing claim of Leea macrophylla scientifically. Material and methods: Box–Behnken design (BBD) was used to optimize the extraction process. The optimized root tuber extract of Leea macrophylla was standardized with chlorogenic acid by HPLC for the first time. Both oral and topical routes were selected as administrative means for the wound healing study using excision and incision wound model. For topical treatment bioadhesive gel was formulated and characterized for mechanical and physical characteristics by texture profile analysis (TPA) and scanning electron microscopy (SEM). The effect on wound healing was also assessed by evaluating antioxidant enzymes viz. glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT), free radicals lipid peroxidation (LPO) and nitric oxide (NO), inflammatory marker myeloperoxidase (MPO), collagen markers hydroxyproline, hexosamine and hexuronic acid along with the histopathological examination. Furthermore, the effect on the level of the proinflammatory cytokines interleukin-1β (IL-1β), interleukin -6 (IL-6), tumor necrosis factor-α (TNF-α) and growth factor, vascular endothelial growth factor (VEGF) were determined. The expression of cell proliferation nuclear marker Ki-67 was also analyzed by Western blot analysis. Results: With mesh openings Sieve no. 20, semi polar nature of solvent (92.5:7.5 ethanol-water blend) and extraction time of 18 h, substantially greater extraction efficiency (29%) and phenolic yield (181.54 mg/g) were obtained. The content of chlorogenic acid in ethanol extracts of Leea macrophylla was obtained as 9.01% w/w. In incision model, oral treatment with 500 mg/kg ethanolic extract increased wound breaking strength by 23.41% while bioadhesive gel (5% w/v) showed a higher increase of 44.68%. Topical application produced complete wound contraction in 20 days against 22 days taken by oral treatment. Topical treatment also produced a significant ( p <0.05) increase in antioxidants glutathione, superoxide dismutase and catalase whereas the level of enzymes lipid peroxidation and nitric oxide and inflammatory markers myeloperoxidase were reduced. Further advantageous effects were reflected by significantly ( p <0.05) increased levels of hydroxyproline, hexosamine and hexuronic acid. Favorable effects on the level of proinflammatory cytokines interleukin-1β, interleukin-6, tumor necrosis factor – α and growth factor, vascular endothelial growth factor were also observed. The wound healing potential of Leea macrophylla was further supported by its ability to promote cell proliferation during wound healing as demonstrated by Western blot analysis of proliferation marker Ki-67. Conclusion: The study justified traditional use of Leea macrophylla in wound healing and demonstrated that the bioadhesive gel of ethanolic extract produced faster and more significant healing as compared to oral treatment. Graphical abstract: